Leaf Polyphenolic Profile as a Determinant of Croatian Native Grapevine Varieties’ Susceptibility to Plasmopara viticola - Štambuk, Petra; Šikuten, Iva; Karoglan Kontić, Jasminka; Maletić, Edi; Preiner, Darko; Tomaz, Ivana (Frontiers in Plant Science, 2022)
Since grapevine is highly susceptible to various microorganisms, enormous amounts of pesticides are applied each season to achieve profitable production. One of the most destructive grapevine diseases is downy mildew, and their interaction has been in the spotlight for more than a decade. When it comes to a metabolome level, phenolic compounds are relevant to investigate due to their involvement in the plant immune system and known antifungal properties. Croatian grapevine germplasm is highly heterogeneous due to its long history of cultivation in diversified geographical regions. Since it has been found that native varieties react differently to Plasmopara viticola infection, the intention of this study is to define leaves’ chemical background, i.e. polyphenolic composition, responsible for these dissimilarities. Therefore, leaves of 17 genotypes, among which 14 were native and 3 were controls, were analyzed using high-performance liquid chromatography in four terms: before inoculation (T0), 24 hours post-inoculation (hpi) (T1), 48 hpi (T2) and 96 hpi (T3). During this early phase, significant differences were found neither between terms nor between non-inoculated and inoculated samples, except for resveratrol-3-O-glucoside. Applying principal component analysis using initial leaf polyphenolic composition, V. vinifera varieties were clearly separated into three different groups corresponding to their OIV classes of susceptibility to P. viticola. Results obtained in this research are suggesting that cultivar initial constitutive polyphenolic composition of leaves has a crucial influence on their susceptibility to P. viticola and this finding can be used to improve the success of grapevine breeding programs towards downy mildew resistance.